2021
DOI: 10.1007/s00148-020-00814-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, climate change, and human conception rates: evidence from Hungary

Abstract: In this paper, we examine the relationship between temperature and human conception rates and project the impacts of climate change by the mid-twenty-first century. Using complete administrative data on 6.8 million pregnancies between 1980 and 2015 in Hungary, we show that exposure to hot temperatures reduces the conception rate in the first few weeks following exposure, but a partial rebound is observed after that. We project that with absent adaptation, climate change will increase seasonal differences in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
(81 reference statements)
1
12
0
1
Order By: Relevance
“…Roughly half of the short-term decline is compensated by a rebound within six months following the exposure. Separately examining conceptions ending in live births, induced abortions, and spontaneous fetal losses, Hajdu and Hajdu (2021a) showed that the initial drop is very similar for all pregnancy outcomes. However, the subsequent rebound of the overall conception rate is driven by conceptions ending in live births.…”
Section: Birth Rates Conception Ratesmentioning
confidence: 97%
See 2 more Smart Citations
“…Roughly half of the short-term decline is compensated by a rebound within six months following the exposure. Separately examining conceptions ending in live births, induced abortions, and spontaneous fetal losses, Hajdu and Hajdu (2021a) showed that the initial drop is very similar for all pregnancy outcomes. However, the subsequent rebound of the overall conception rate is driven by conceptions ending in live births.…”
Section: Birth Rates Conception Ratesmentioning
confidence: 97%
“…The recent paper of Hajdu and Hajdu (2021a) went one step further and examined the impact of preconception temperatures on conception rates between 1980 and 2015 in Hungary. The conception rate was calculated from all clinically recognized pregnancies (live births, induced abortion, miscarriages, stillbirths).…”
Section: Birth Rates Conception Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing temperatures are also expected to increase demand for public goods. For instance, they may create additional demand for healthcare, given that higher temperatures are linked to excess morbidity and mortality, e.g., due to heat strokes and other cardiovascular ailments, difficulties during pregnancy, mood disorders and exhaustion and even suicidality as well as the spread of infectious diseases when increasing temperatures allow insects and rodents that are disease vectors (e.g., mosquitos for malaria) to find new habitats in regions that were previously too cold (e.g., Berry et al 2010;Deschenes 2014;Wu et al 2016;Burke et al 2018;Chen et al 2020;Meierrieks 2021;Hajdu and Hajdu 2021; for overviews of the nexus between climate change, human health and migration, see, e.g., McMichael et al 2012;Schwerdtle et al 2018). Similarly, there may be increased demand for order and security, given that global warming may undermine social stability.…”
Section: Public Goodsmentioning
confidence: 99%
“…Compared with mortality, research on the impact of heat on such outcomes has been more limited. Despite some recent interest in the impact of heat on fertility and birth outcomes, there remain many unresolved questions on this topic (Barreca et al., 2018; Chersich et al., 2020; Hajdu & Hajdu, 2022). The mechanisms linking temperature with fertility are still debated and are critical to comprehending how heat shapes reproductive health and behavior in a world with low fertility rates and an aging population.…”
mentioning
confidence: 99%